The Enactment of Online Learning for Special Need Students during COVID 19 Pandemic: A Case Study - Saharudin, Saharudin; Sulistiyo, Urip; Handayani, Reli; Setyonegoro, Agus; Prasetyoningsih, Luluk Sri Agus (Jurnal Ilmu Pendidikan, 2022)
The present study focuses on the implement of online learning in special education and how Information and Telecommunications Technology being used to strengthen and support the achievement of learning and the learning goals at special needs junior high school students (SMPLB) Jambi. The research method used in this study is a case study where the researchers observe how the patterns and processes of online education in the learning of SMPLB students, distributing questionnaires on the use of ICT to the teachers, interviews with parents/guardians of the students, and interviews with special junior high school teacher Sri Soedewi Maschun Sofyan, S.H Jambi. The results of the research indicate that the students in special needs schools have difficulty in obtaining technology that suits with their needs in learning. The learning process cannot be carried out as expected because the teachers have difficulty in making technology-based learning materials for the students, especially for students with the deaf and the blind. Reading and writing skills are also very limited, and the student learning is very low because the online method greatly limits opportunities for direct interaction between the students and the teachers. The involvement of parental assistance is also very low because the parents do not understand how to aid with children in online learning.